Plasma membrane is the target of rapid antibacterial action of silver nanoparticles in Escherichia coli and Pseudomonas aeruginosa - Bondarenko OM (Dove Medical Press, 2018)
Olesja M Bondarenko,1 Mariliis Sihtmäe,1 Julia Kuzmičiova,2 Lina Ragelienė,2 Anne Kahru,1,3 Rimantas Daugelavičius2 1Laboratory of Environmental Toxicology, National Institute of Chemical Physics and Biophysics, Tallinn 12618, Estonia; 2Department of Biochemistry, Vytautas Magnus University, Kaunas LT-44404, Lithuania; 3Estonian Academy of Sciences, Tallinn 10130, Estonia Introduction: Silver nanoparticles (AgNP) are widely used in consumer products and in medicine, mostly due to their excellent antimicrobial properties. One of the generally accepted antibacterial mechanisms of AgNP is their efficient contact with cells and dissolution in the close vicinity of bacterial cell envelope. Yet, the primary mechanism of cell wall damage and the events essential for bactericidal action of AgNP are not elucidated. Materials and methods: In this study we used a combination of various assays to differentiate the adverse effects of AgNP on bacterial cell envelope: outer membrane (OM) and plasma membrane (PM). Results: We showed that PM was the main target of AgNP in gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa: AgNP depolarized PM, induced the leakage of the intracellular K+, and inhibited cellular respiration. The results of bacterial bioluminescence inhibition assay in combination with AgNP dissolution and oxidation assays demonstrated that the adverse effects of AgNP occurred at concentrations 7–160 µM. These toxic effects occurred already within the first few seconds of contact of bacteria and AgNP and were driven by dissolved Ag+ ions targeting bacterial PM. However, the irreversible inhibition of bacterial growth detected after 1-hour exposure occurred at 40 µM AgNP for P. aeruginosa and at 320 µM AgNP for E. coli. In contrast to effects on PM, AgNP and Ag+ ions had no significant effect on the permeability and integrity of bacterial OM, implying that AgNP indeed targeted mainly PM via dissolved Ag+ ions. Conclusion: AgNP exhibited antibacterial properties via rapid release of Ag+ ions targeting the PM and not the OM of gram-negative bacteria. Keywords: antimicrobials, mechanism of toxicity, gram-negative, inner membrane, outer membrane, nanomaterials, collargol, bioluminescence